Routemap for health impact assessment implementation: scoping review using the consolidated framework for implementation research. - Kenny, Tara; Harris-Roxas, Ben; McHugh, Sheena; Douglas, Margaret; Green, Liz; Haigh, Fiona; Purdy, Joanna; Kavanagh, Paul; O'Mullane, Monica (Health Promotion International, 2025)
Health Impact Assessment (HIA) provides a practical set of tools to appraise the potential health effects of a policy, programme, or project prior to implementation. HIA has gained significant attention in recent decades due to its utility in facilitating a broader understanding of health and bringing diverse stakeholders and evidence into decision-making processes. Despite this interest in HIA its implementation remains challenging within governance, decision making, and regulatory contexts. The Consolidated Framework for Implementation Research (CFIR) 2.0 provides a methodological framework to identify potential factors influencing implementation and the domains in which they operate, within the framework. For the purpose of this scoping review, implementation refers to the process of carrying out an HIA, and where applicable, the implementation of its recommendations. This review presents a novel exploration of HIA from an implementation science perspective. It provides a synthesis of the factors influencing HIA implementation and identifies a range of considerations and strategies that may facilitate and strengthen HIA implementation and support. The findings suggest that the earlier steps are critical in assisting the practical application and implementation of HIA. However, building wider HIA support, awareness, and capacity essential to progressing HIA is dependent on wider public health advocacy and addressing challenges specific to HIA as a method and tool. CFIR offers a useful and adaptable framework that could be used for supporting HIA planning, practice, and implementation.